Philippine standard word list grades I-VII - Casambre, Alejandro J. (Bureau of Public Schools, Department of Education, 1953)
This Philippine standard word list is a compilation of 13,150 words. It is the result of several vocabulary studies conducted in 1934 by various committees under the direction of J. Scott McCormick, Chief of the Academic Division of the Bureau of Education at the time, with the assistance of Dr. Manuel L. Carreon, then head of the section on Measurement and Research. The compilation, which took more than two years, is based on the vocabulary of the basic texts and supplementary readers in use at the time in grades I-VII and on the vocabulary of the public school children in these grades. Samples of the different textbooks and supplementary readers were examined for their vocabulary content. The vocabulary of the pupils, on the other hand, was determined from samples of their written work, from common words used in spelling tests, and from an alphabetical list of key words issued to the schools. The pupils in a number of schools listed all the words they knew that were suggested by each key word.--Foreword.